From biomechanical theory to application in top sports: the Klapskate story - de Koning, J. J.; Houdijk, H.; de Groot, G.; Bobbert, M. F. (Journal of Biomechanics, 2000)
Although it was hypothesized from theory that the benefits of the klapskate could result in improved speed skating performances, the klapskate was only able to demonstrate its advantage over conventional skates after the speed skaters adopted the idea and started to use them. Scientific data to prove the benefits of the klapskate and to convince elite athletes to change their equipment were not available for a long time. In fact, at this moment practice runs ahead: top skaters skate world records while we are struggling to understand from biomechanical, exercise physiological, as well as from computer simulation data why skating on klapskates is so much faster than skating on conventional skates.